THE EFFECT OF LEARNING MEDIA AND INTEREST IN LEARNING ON ENGLISH LEARNING OUTCOMES - Reni Apriani (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2019)
This study aims to determine the Effect of Learning Media Influence and Interest in Learning Outcomes of English in Public Junior High School Students in Lebak Banten. Furthermore,the researcher to find out the effect of learning media interaction and learning interest on learning outcomes using the quantitative experiment method. This study used population of 583 students and sample of 70 students. The research hypotheses tested include: 1) There is a significant effect of learning media on learning outcomes. 2) There is a significant effect of interest in learning on learning outcomes. 3) There is a significant interactive influence on learning media and interest in learning about learning outcomes. Then from the results of the hypothesis test, it was found that 1) there is a significant effect of learning media on the learning outcomes of English students of Lebak region at Junior High School. This is evidenced by the acquisition of the Sig. = 0,000 <0,05 and F count = 16,334. 2) There is a significant effect of interest in learning on the learning outcomes of English students in Lebak region at Junior High School. This is evidenced by the acquisition of Sig. = 0,000 <0,05 and F count = 15,127. 3) There is a significant interaction effect of learning media and learning interest in the learning outcomes of English students of Lebak region Junior High School. This is evidenced by the acquisition of Sig. = 0,000 <0,05 and F count = 13,833.